STIMULASI BRAIN GYM DALAM RANGKA MENDUKUNG PERKEMBANGAN ANAK PRASEKOLAH DI PAUD DAN TK TUAH BERSAMA DESA LEMBAH ALAS - Halimatussakdiyah Lubis HALIMAH; Yusnaini; Siska Putri Belangi (Amal Insani Foundation, 2023)
The Brain Gym program is a way to stimulate children, can improve children's gross motor skills, increase concentration, and reduce anxiety levels. The socialization activity for the Brain Gym program was held at PAUD and TK Tuah Bersama 1 (for one) month from November 15 to December 16 2022 with 5 teachers as cadres, and 30 students from PAUD and TK Tuah Bersama. The training process for Brain Gym activities was carried out by playing the Brain Gym video, and the community service team became role models, together with 5 teachers who became cadres conducting Brain Gym for PAUD and TK Tuah students with Lembah Alas Village. Participants were very enthusiastic during the socialization process, and not a single person left the series of events. Participants have received material socialization regarding Brain Gym, toilet training, and 7 ways to wash hands through the Brain Gym stimulation program and still need further socialization and assistance related to the Brain Gym program to support the development of preschoolers.